The Effectiveness of Green Marketing in Shaping Sustainable Consumer Behavior: A Critical Narrative Review - Purnama, Yunus Indra (JURNAL KEWIRAUSAHAAN, AKUNTANSI DAN MANAJEMEN TRI BISNIS, 2026)
The growing importance of environmental issues has encouraged firms to adopt green marketing Environmental challenges are becoming more and more important, which has prompted businesses to use green marketing techniques and inspired customers to take more sustainable behaviors. This study uses a critical narrative literature review to investigate how advancements, tactics, and difficulties in green marketing impact sustainable consumer behavior. A systematic search of the major academic databases, such as Scopus, Web of Science, and Google Scholar, encompassing works published from 2010 to 2025, was used to conduct the literature review. Relevance screening was used to choose 78 peer-reviewed journal articles based on their topical alignment, publishing quality, and contribution to the subjects of sustainable consumption and green marketing. The review outlines important tactics for eco-labeling, sustainable product creation, green branding, and digital communication based on the chosen body of research. It also looks at sociodemographic, cultural, and psychological aspects that influence the success or failure of sustainable consumption. This article also addresses frequent issues, such as consumer mistrust, greenwashing tactics, legal restrictions, and the discrepancy between consumer intentions and actual behavior. Emerging themes are also emphasized as viable avenues for the future, including circular economy projects, green digital nudging, and the use of technology to increase transparency. According to the review, long-term behavioral research, interdisciplinary techniques, and cross-cultural studies should be prioritized in future studies. For marketers, legislators, and academics looking to more successfully apply green marketing techniques and promote truly sustainable consumer behavior, these findings offer insightful information.